Comparative Analytical Study of the Social Dimension Between Traditional and Contemporary Urban Environments: Case Study of Riyadh - Alhumaidi د.علي; Al Khayyal عبدالله (Journal of King Abdulaziz University: Environmental Design Sciences, 2022)
Abstract This paper is mainly concerned with the relationship between social dimensions and the built environment in residential neighborhoods. The study focuses on the imbalance in social functions in accordance to the performance of the urban residential environments, by comparing two types of residential environments, traditional neighborhoods and contemporary neighborhoods. In the past, residential neighborhoods provided good social cohesion among residents on all neighborhood levels. On the other hand, contemporary neighborhoods show a noticeable decline in some important social dimensions such as privacy, security, safety, communication and social interaction. Therefore, this study aims to shed some light on the differences between traditional and contemporary neighborhoods with regard to the social dimensions of urban space. The study also aims to recommend some measures to improve these social dimensions by taking advantage of lessons from the past and extrapolating it through the use of qualitative methods. Tools such as interviews were used to collect information and to analyze study models of both types of neighborhoods. The study concluded that privacy in traditional neighborhoods was the most important social dimension, which in turn enhanced other social dimensions such as security, safety and social interaction. On the other hand, the lack or decline of privacy in contemporary neighborhood has affected negatively other social dimensions in the built environment